APPROPRIATENESS OF CARDIOVASCULAR PREVENTIVE MEDICATION IN OLDER PEOPLE: A QUALITATIVE RAM-STUDY. (June 2022) - Ploeg, Milly Van Der; Poortvliet, Rosalinde; Achterberg, Wilco; Mooijaart, Simon; Gussekloo, Jacobijn; Drewes, Yvonne
Abstract : Objective: In clinical practice and science, there is debate for which older adults the benefits of cardiovascular preventive medications (CPM) still outweigh the risks in older age. Therefore, we aimed to assess how various clinical characteristics influence the judgement of appropriateness of CPM (i.a. antihypertensive treatment) in older adults. Design and method: With the RAND/ University of California at Los Angeles appropriateness Method (RAM) the appropriateness of CPM for adults = > 75 year was assessed with regard to clinical characteristics (cardiovascular history, complexity of health problems, age, side-effects and life expectancy). A multi-disciplinary panel (n = 14 panelists) received an up to date overview of the literature, and judged the appropriateness of starting and stopping cholesterol lowering medication, antihypertensives, and platelet aggregation inhibitors, on 1- to 9 point Likert scales (1 = extremely inappropriate; 9 = extremely appropriate), for various clinical scenarios. There were two rating rounds, with one face-to-face discussion in between. The appropriateness judgments were based on the median panel rating and level of disagreement Results: The panelists emphasized the importance of the individual context of the patient for appropriateness of CPM. They judged that in general, a history of atherosclerotic cardiovascular disease (ASCVD) strongly adds to the appropriateness of CPM, while increasing complexity of health problems, presence of hindering or severe side-effects, and life expectancy < 1 year all contribute to the inappropriateness of CPM. Age had only minor influence on the appropriateness judgments. The appropriateness judgments were different for the three types of CPM. The literature, time-to-benefit, remaining life-expectancy, number needed to treat, and quality of life, were major themes in the panel discussions. The considerations to stop CPM were different from the considerations not to start CPM. Conclusions: Next to the patients' individual context, which was considered decisive in the final decision to start or stop CPM, there were general trends of how clinical characteristics influenced the appropriateness, according to the multi-disciplinary panel. The decision to stop, and not start CPM, appeared to be two distinct concepts. Results of this study may be used in efforts to support clinical decision making about CPM in older adults.